2017
DOI: 10.7189/jogh.07.010501
|View full text |Cite
|
Sign up to set email alerts
|

Fukushima after the Great East Japan Earthquake: lessons for developing responsive and resilient health systems

Abstract: BackgroundOn 11 March 2011, the Great East Japan Earthquake, followed by a tsunami and nuclear–reactor meltdowns, produced one of the most severe disasters in the history of Japan. The adverse impact of this ‘triple disaster’ on the health of local populations and the health system was substantial. In this study we examine population–level health indicator changes that accompanied the disaster, and discuss options for re–designing Fukushima’s health system, and by extension that of Japan, to enhance its respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Overall, the empirical studies identified differed in terms of their disciplinary tradition or conceptual background. Studies from the public health sciences tended to converge in three groups: (1) quantitative studies focusing on service delivery, making use of service utilization indicators provide an easily accessible measure to assess resilience before, during and after a crisis ( Paterson et al 2014 ; Gizelis et al 2017 ; Sochas et al 2017 ; Kozuki et al 2018 ; Ray-Bennett et al 2019 ), (2) qualitative studies focusing on the health workforce, influenced by ideas of ‘everyday resilience’ and addressing the contributions of social connectedness and leadership on health system resilience ( Mash et al 2008 ; Witter et al 2017 ; Raven et al 2018 ; Brooke-Sumner et al 2019 ; Thude et al 2019 ), and (3) studies taking a broad perspective of health system resilience, looking at multiple health system building blocks or aspects of a health system to assess resiliency ( Ager et al 2015 ; Ammar et al 2016 ; Fukuma et al 2017 ; Ling et al 2017 ; Meyer et al 2018 ; Watts et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the empirical studies identified differed in terms of their disciplinary tradition or conceptual background. Studies from the public health sciences tended to converge in three groups: (1) quantitative studies focusing on service delivery, making use of service utilization indicators provide an easily accessible measure to assess resilience before, during and after a crisis ( Paterson et al 2014 ; Gizelis et al 2017 ; Sochas et al 2017 ; Kozuki et al 2018 ; Ray-Bennett et al 2019 ), (2) qualitative studies focusing on the health workforce, influenced by ideas of ‘everyday resilience’ and addressing the contributions of social connectedness and leadership on health system resilience ( Mash et al 2008 ; Witter et al 2017 ; Raven et al 2018 ; Brooke-Sumner et al 2019 ; Thude et al 2019 ), and (3) studies taking a broad perspective of health system resilience, looking at multiple health system building blocks or aspects of a health system to assess resiliency ( Ager et al 2015 ; Ammar et al 2016 ; Fukuma et al 2017 ; Ling et al 2017 ; Meyer et al 2018 ; Watts et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight studies which assessed an entire, national health system in the context of a particular crisis, two studies took a purely quantitative approach: Fukuma et al (2017) assessed Japan’s health system responsiveness and resilience after the Great East Japan Earthquake and Watts et al (2018) assessed the resilience of 101 health systems in the context of climate change. Fukuma et al (2017) operationalized resilience by using composite routine data indicators during the time of crisis, including: service utilization, cause-specific mortality rates incl. suicides, number of hospitals, health expenditures, human resources and immunization coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike violence initiated by humans, natural disasters may leave community trust intact or bolster cooperation. In some settings, natural disasters are associated with reductions in violent crime [29][30][31], increases in family functioning [32,33], and prosocial behavior in communities and families [34][35][36]. One such study on communities affected by Hurricane Andrew found that one-third of respondents reported less stress with their neighbors than before the disaster, and 90% felt that the sense of sharing had been high in the neighborhood immediately after the hurricane and one year later [37].…”
Section: Introductionmentioning
confidence: 99%
“…A resilient health system can absorb the shock of an emergency while continuing to provide regular health services. [6][7][8] Most frameworks for building resilient health systems that effectively respond to disease outbreaks focus on enhancing preparedness or response capacity prior to an emergency [9][10][11] or to strengthen health systems after the emergency, typically during the recovery phase. Indeed, many aspects of outbreak response lay the groundwork for health system strengthening (HSS), such as enhancing surveillance systems and training the health workforce.…”
Section: Summary Boxmentioning
confidence: 99%